Lateral Asymmetry in Speech Processing at the Brainstem: Evidence from Speech Evoked ABR - Sujith Kumar Sinha; Vijayalakshmi Basavaraj (Journal of All India Institute of Speech and Hearing, 2010)
Asymmetrical function of the left and right cerebral cortices is well documented. Rapidly changing auditory signals (including speech) are primarily processed in the left auditory areas while tonal stimuli are preferentially processed in the right hemisphere. Some studies suggest that response asymmetries in subcortical auditory structures do exist and may contribute to cerebral lateralization. However, the role of the subcortical auditory pathway in lateralized processing needs to be further established. 40 normal hearing subjects participated in the study. Click evoked auditory brainstem response (ABR) and speech evoked ABR were recorded. Speech evoked ABR was elicited using a synthesized /da/ stimulus. The two measures of speech evoked ABR the onset response (consist of wave V) and the frequency following responses (consist of wave D, wave E, and wave F). Additional, a fast fourier transform (FFT) of FFR also gives information regarding the amplitude of fundamental frequency of sound, the amplitude of first formant of the sound and higher harmonics of the speech sound. Results revealed that there was no difference between wave V of click evoked and speech evoked ABR for the left and the right ear. But the mean latency of wave D, E, F and O were shorter for the right ear as compared to that for the left ear. Also, the frequency following responses (FFR) revealed that mean amplitude of fundamental frequency and harmonics were larger for the right ear as compared to the left ear. The present study suggests that the right ear advantage for speech stimulus could be preserved at the brainstem level. The study adds new information in the role of auditory brainstem processing of speech sounds. These results may open up new area of research in clinical population such as learning disabled children and also the older individuals.